Pengaruh moderasi koneksi politik terhadap kepemilikan keluarga dan agresivitas pajak - Widya Hidayati; Vera Diyanty (Jurnal Akuntansi dan Auditing Indonesia, 2018)
The study aims to prove moderating effect of political connection to family ownership and how it affects corporate tax aggressiveness. This research contain all non-financial listed companies on Indonesia Stock Exchange from 2010 to 2013 by using purposive sampling method and regression for data analysis. Tax aggressiveness is measured through Effective Tax Rate (ETR) and Current Effective Tax Rate (CETR). The results show that family ownership negatively affects corporate tax aggressiveness and moderation of political connections will weaken the negative effects of family ownership. The result of this study proven that ownership characteristics and political connection can be used by Directory of General Tax (DGT) to measure the risk of company involvement in tax aggressive activities.